Not dead yet: cell death and survival in cancer and normal physiology - Green, Douglas R. (Frontiers in Cell Death, 2024)
For decades, we have assumed that all regulated cell death pathways have a dedicated "point of no return" that precedes death but aPer which cells are commiQed to die. The realizaSon that this is oPen not the case represents what can be considered a paradigm shiP in the field. Here we consider how cells can survive despite engagement of a cell death pathway and the consequences of a "near death experience" in cancer cells and possibly other physiological condiSons.Running Stle: Surviving cell death pathway engagement IntroducSon How cells die is a fundamental aspect of the biology of the cell, and as such, it is realisSc to assume that despite decades of research into the various modes and pathways of cell death, we conSnue to have a great deal to learn. Perhaps paradoxically, the field of cell death remains vibrantly alive, as evidenced by the frequent advances and publicaSons in this realm of molecular and cellular biology.